Governing Montreal - Sancton, A; Sancton, Andrew 1948- (1978)
﻿ In comparison with Toronto and Winnipeg, structural reform of metropolitan governmental institutions in Montreal has taken considerably longer and has been far less comprehensive. Why? The main objective of this thesis is to answer this question. The answer centres mainly on the existence of two major linguistic communities--a condition not present in the other two cities. The thesis suggests that there have been three different varieties of motivational factors behind the metropolitan reform movement in Montreal: 1) the need to establish new metropolitan institutions to respond to particular crises resulting from the breakdown of local government services; 2) the desire to establish a set of metropolitan structures which meet the requirements of organizational rationality; and 3) the desire of Quebec nationalists to re-arrange local institutions in such a way as to eliminate any official recognition of the English-speaking minority. The first variety of factors serves to explain the creation of the Montreal Urban Community in 1969. The second variety was behind the attempts in the early 1970s to restructure municipal boundaries, to integrate the various municipal police forces, and to re-organize the social service network. The third variety has been important primarily in relation to debates about the re-organization of Montreal's school boards. Judging from recent events, it is likely to become even more apparent in other fields in the near future. Insofar as organizational rationality involves the simplification of governmental structures, the aims of many Quebec nationalists are likely to promote this type of reform rather than hinder it. However, in Montreal, unlike Toronto and Winnipeg, reforms justified solely on the basis of organizational rationality have either not been implemented at all or have been done so in a very slow or modified manner. This can be explained prinarily in terms of the impact of Montreal's linguistic cleavage.